EPIDEMIOLOGICAL AND CLINICAL PROFILE OF MEN WITH BREAST CANCER IN AMAZONAS, BRAZIL - Carvalho Neto, Antônio Cosme; Nunes, Gabriel Pacífico Seabra; Pereira, Hilka Flávia Barra do Espirito Santo Alves (Mastology, 2019)
The aim of the present study was to determine the epidemiological and clinical profile of men diagnosed with breast cancer at the Oncology Center Foundation (FCECON) of the state of Amazonas, Brazil. Male breast cancer is a rare disease, accounting for about 0.2% of all cancers, and it is responsible for 0.1% of male cancer deaths. Despite the rarity of the disease, statistics indicate that the incidence of male breast cancer has increased significantly from 0.86 to 1.06 per 100,000 men over the past 26 years. We conducted a retrospective longitudinal descriptive study of the medical records of male patients diagnosed with breast cancer from 2001 to 2013. In this study, there was a greater number of cases with ages over 55 years (83.54%), compared to an average age of 60‑70 years reported in the literature. The histological type of the tumors analyzed was predominantly infiltrating ductal carcinoma (76.46%). We observed that tumors in stages IIIA and IIIB made up the majority of cases (58.82% in total), which was due to the patients’ late search for medical care. There are no records of previous studies that address breast cancer in men in Amazonas, so we hope that our findings contribute relevant information about breast cancer in the state of Amazonas.